PENANAMAN NILAI-NILAI BUDI PEKERTI MELALUI TEMBANG DOLANAN ANAK-ANAK PADA ANAK USIA DASAR - M.A Dhalu (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2020)
This study aims to retain the children’s songs in Srimulyo Village and the games that have now been forgotten and many of which are unknown to children in the village. The result of this research is that tembang dolanan has a very important character value in growing confidant independent responsibility and some of the character that needs to be shaped in children. The importance of dolanan song which is a cultural heritage is maintained until now, namely the value of education contained in it that teaches children to prosses good values, religious values, social values, and cultural values. The method used in this research is descriptive research methods qualitative. The instruments in this study were individual research, data collection, and interviews with resource persons. From the result of data acquisition in the field, there are a number of children’s songs which from each stanza have different meanings and values of education and teach about the values of character, religious values, cultural values, and social values that can be known from analyzing the meaning of children’s song